2018
DOI: 10.1038/s41598-018-21045-1
|View full text |Cite
|
Sign up to set email alerts
|

Terpene Composition Complexity Controls Secondary Organic Aerosol Yields from Scots Pine Volatile Emissions

Abstract: Secondary organic aerosol (SOA) impact climate by scattering and absorbing radiation and contributing to cloud formation. SOA models are based on studies of simplified chemical systems that do not account for the chemical complexity in the atmosphere. This study investigated SOA formation from a mixture of real Scots pine (Pinus sylvestris) emissions including a variety of monoterpenes and sesquiterpenes. SOA generation was characterized from different combinations of volatile compounds as the plant emissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 55 publications
7
83
0
Order By: Relevance
“…The known OH reactivity for pine emissions is dominated by monoterpenes with a small fraction of sesquiterpenes as expected from earlier studies (Tarvainen et al, 2005;Hakola et al, 2006;Yassaa et al, 2012;Bäck et al, 2012;Faiola et al, 2018).…”
Section: Pinesupporting
confidence: 75%
“…The known OH reactivity for pine emissions is dominated by monoterpenes with a small fraction of sesquiterpenes as expected from earlier studies (Tarvainen et al, 2005;Hakola et al, 2006;Yassaa et al, 2012;Bäck et al, 2012;Faiola et al, 2018).…”
Section: Pinesupporting
confidence: 75%
“…Additionally, using monoterpene-specific SOA yields where available resulted in SOA predictions ∼1.5−2.5× higher than applying the α-pinene SOA yield to all measured monoterpenes (as is conventional in many model representations of SOA formation from monoterpenes; Figure 1d), in general agreement with similar analysis of monoterpenes emitted from stressed Scots pine. 38 Although the contribution of terpenoids to SOA production in smoke from wildland fires remains largely unquantified, these results illustrate that chemically speciating such emissions will be essential for fully and accurately elucidating their chemistry.…”
Section: ■ Implicationsmentioning
confidence: 99%
“…For example, one recent study found that accounting for monoterpene complexity in Scots pine (Pinus sylvestris) emissions led to 1.5−2.3× higher predicted SOA formation than assuming α-pinene as a single, representative surrogate compound. 38 Heating of vegetation causes substantial release of resin constituents via distillation out of storage ducts/glands, 39−44 demonstrating the potential for high emissions of terpenoids during vegetation fires of resinous fuels. Although a few studies have observed high total terpenoid emissions from wildland fires, 45−47 there have been relatively few measurements of speciated terpenoid emissions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…MTs can have relatively high concentrations in conifer root tissues while emissions are rather low (Lin et al 2007). Reason for this could be that MTs are reactive, rapidly degrade in the air (Faiola et al 2018), adsorb on various surfaces (Schaub et al 2010) or diffuse in soil water (Hiltpold and Turlings 2008). Therefore, a considerable proportion of volatile isoprenoids existing in the rhizosphere may not diffuse from the soil to the atmosphere (Lin et al 2007).…”
Section: Bvocs Of Rhizosphere Litter and Understorymentioning
confidence: 99%